Factors For Determining The Effective Tax Rate For Infrastructure Companies For The 2018-2022 Period - Teddy Haryadi; Hadli Lidya Rikayana; Nurul Yusyawiru (Cita Konsultindo Research Center, 2024)
Income smoothing is one form of management and company leadership to manage the gradual increase in company profits every year. The purpose of this study is to see the effect of Return on equity, Debt to total assets, and Current Ratio on income smoothing with effective tax rates as mediation variables. The Effective Tax Rate as a mediating variable is expected to affect the relationship between Return on equity, Debt to total assets, and Current Ratio to income smoothing. This is because tax is one form of company obligation that will increase with an increase in profits obtained by the company. The object of research is all companies engaged in the Infrastructure sector on the Indonesia Stock Exchange, the analysis period is the financial report year 2018 to 2022. The number of companies that meet the criteria is 18 companies. Data analysis technique using Partial Least Square method with WarpPLS 8.0 application. Based on the results of the analysis, Return on equity and Debt to total assets do not affect Income smoothing. The current Ratio and Effective Tax Rate have a positive effect on Income smoothing. Return on equity and Debt to total assets negatively affect the effective tax rate. The Current Ratio has a positive effect on the effective tax rate. This study also shows that effective tax rates can mediate the relationship between the Current Ratio to Income smoothing. The effective tax rate cannot mediate the relationship of Return on equity and Debt to total assets to Income smoothing. Return on equity, Debt to total assets, Current Ratio, and the effective tax rate can affect income smoothing by 11%.